From Barriers to Outcomes: A Systematic Review of Global Citizenship Education in Higher Education Toward Sustainable Development Goals (2015–2025) - Husnul Fatihah; Kokom Komalasari; Rahmat Rahmat; Dadang Sundawa; Iim Siti Masyitoh; Asep Mahpudz (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
Global Citizenship Education (GCE) has become increasingly important in preparing young people with global awareness, intercultural empathy, ethical values, and critical thinking skills needed to address contemporary global challenges and contribute to the Sustainable Development Goals (SDGs). This study aims to provide a comprehensive overview of the implementation of GCE in higher education through publications indexed in Scopus and Web of Science (WoS) from 2015 to 2025. The study employed a Systematic Literature Review (SLR) method based on the PRISMA framework, including data searching, screening, eligibility assessment, and thematic synthesis. A total of 380 articles were identified, and 57 articles met the inclusion criteria for further analysis. The findings reveal that GCE research is still dominated by developed countries, while contributions from developing countries remain limited. Most studies adopted qualitative approaches and highlighted the positive impacts of GCE in promoting peace, tolerance, global solidarity, intercultural competence, and support for the SDGs. However, several challenges persist, including curriculum integration, cultural and ideological barriers, and limited educator capacity. The study recommends strengthening GCE curricula in higher education through approaches that integrate local and global perspectives to foster inclusive and sustainable global citizenship.